Finite amplitude electro-thermo convection in a cubic box. (1st December 2022) - Peng, Yu-xing; Liu, Qiang; Li, Zhong-xian; Wu, Jian
Abstract: Three-dimensional electro-thermo-hydrodynamic (ETHD) flows of dielectric fluids driven by simultaneous Coulomb and buoyancy forces in a cubic box is numerically studied. The set of coupled equations associated with the ETHD phenomena are solved with the finite volume method. The code is first validated by comparing the numerically obtained linear critical values of the pure electro-convection and thermal convection with the previous studies. Then the neutral stability curve of the system is given and the finite amplitude instability thresholds with different Rayleigh numbers ( Ra ) are presented. It is found that along the neutral stability curve, the flow strength becomes weaker with the increase of Ra and the decrease of electric Rayleigh number ( T ). Besides, the gap between the linear and nonlinear critical values expressed in terms of T decreases with the increase of Ra . Primarily, the distributions of charge density, temperature and velocity fields with different governing parameters near neutral stability curve are presented. The temperature and charge density profiles near the linear and nonlinear critical values are given, showing that higher T results in wider charge void region and shorter distance between the charge void region's lower boundary and injection electrode. Finally, the symmetries of the flow patterns along the neutral stability curve are also discussed briefly.